Solar Chimney for Natural Ventilation in Medtrania Climate - Khalifa B. Alrbee; Mohamed M. Albarghot; Abdullah A. Ahmed (African Journal of Advanced Pure and Applied Sciences, 2024)
The study aims to investigate the possibility of minimizing the heat gain through the outside walls of closed enclosures in order to obtain thermal comfort. Consequently, the enclosure’s natural ventilation is achieved by air drains through an attached solar chimney. A mathematical model was developed to predict the performance of the solar chimney. The geometrical and operational parameters were considered. These parameters include: incident solar radiation, wind speed, ambient temperature and the dimensions of the solar chimney, height, gap and width. Moreover, various chimney cover materials were examined. A computer program was developed to solve the governing energy and conservation equations simultaneously. The model results were compared with the available published data. A good agreement was observed between the developed model results and the published data.